A 1D radiative transfer benchmark with polarization via doubling and adding. (November 2017) - Ganapol, B.D.
Highlights: Doubling and adding method of solving the 1D, azimuthally integrated Stokes 2-vector radiative transfer equation. Numerical solution enhanced through convergence acceleration. Includes seven-place benchmarks of previously limited precision benchmarks found in the literature. A conservative medium benchmark included. Application to light transport in a damaged medium. Abstract: Highly precise numerical solutions to the radiative transfer equation with polarization present a special challenge. Here, we establish a precise numerical solution to the radiative transfer equation with combined Rayleigh and isotropic scattering in a 1D-slab medium with simple polarization. The 2-Stokes vector solution for the fully discretized radiative transfer equation in space and direction derives from the method of doubling and adding enhanced through convergence acceleration. Updates to benchmark solutions found in the literature to seven places for reflectance and transmittance as well as for angular flux follow. Finally, we conclude with the numerical solution in a partially randomly absorbing heterogeneous medium.